How I Do It Afferent Loop Obstruction (ALO) With Hyper-Amylasemia And Deranged Liver Function Test, Are We Going To See This Complication More Frequently Again? - Al-Ardah, M; Shetty, D; Finlay, I (British Journal Of Surgical Science, 2023)
Afferent loop syndrome is a known complication of gastric surgery, specifically after Billroth II and to a lesser extent a Roux–en–Y reconstruction. However, the incidence decreased over the years proportionally with the decrease in the number of gastric surgeries. Afferent loop syndrome can be either acute or chronic, with different presentations and treatment options. The acute type can occur early postoperatively or it could be a delayed presentation. Acute ALS is associated with complete closed-loop obstruction and is considered a surgical emergency, whereas chronic ALS is mostly related to partial obstruction of the afferent loop. This rare complication can occur after the single anastomosis gastric bypass (Omega loop bypass) as it is a type of Billroth II reconstruction of gastric pouch–jejunostomy. With the increase in the number of SAGB performed all over the world as weight reduction surgery for morbidly obese patient s surgeons should be aware of this complication and the treatment options.